Effect of Mangosteen’s fruit peel extract toward to total cholesterol, LDL, HDL serum in rats were given by used cooking oil - Loo Hariyanto Raharjo; Monica Monica (Universitas Wijaya Kusuma Surabaya, 2015)
Waste cooking oil causes increased level of total cholesterol and LDL and decreased level of HDL serum, which became coronary heart disease. The aim of this study was to evaluate the effect of mangosteen peels extract, which contain alpha-mangostin (xanthone) to decreased level of total cholesterol and LDL and increased level of HDL in rats exposed to waste cooking oil per oral. This study used true experimental designs with randomized post-test only control group design. This study used thirty rats were dividing into six treatment group, which control with Na-CMC 0,5%, control with extract of mangosteen pericarp at dosages of 800 mg/ kg body weight, exposed to waste cooking oil per oral, and exposed to waste cooking oil per oral with extract of mangosteen pericarp at dosages of 600, 800, and 1000 mg/kg body weight. All groups were given treatment for 12 weeks. After 12 weeks, rats were anesthetized with chloroform for collection of blood by cardiac puncture. Analysis of level of total cholesterol , LDL, and HDL serum with spectrophotometer. From Post Hoc test with Least Significant Differences it was concluded that extract of mangosteen peels can decreased level of total cholesterol and LDL and increased level of HDL serum.